The Role of MicroRNAs in Early Chondrogenesis of Human Induced Pluripotent Stem Cells (hiPSCs) - Stelcer, Ewelina (Int J Mol Sci, 2019)
Human induced pluripotent stem cells (hiPSCs) play an important role in research regarding regenerative medicine. Particularly, chondrocytes differentiated from hiPSCs seems to be a promising solution for patients suffering from osteoarthritis. We decided to perform chondrogenesis in a three-week monolayer culture. Based on transcriptome analysis, hiPSC-derived chondrocytes (ChiPS) demonstrate the gene expression profile of cells from early chondrogenesis. Chondrogenic progenitors obtained by our group are characterized by significantly high expression of Hox genes, strongly upregulated during limb formation and morphogenesis. There are scanty literature data concerning the role of microRNAs in early chondrogenesis, especially in chondrogenic differentiation of hiPSCs. The main aim of this study was to investigate the microRNA expression profile and to select microRNAs (miRNAs) taking part in early chondrogenesis. Our findings allowed for selection crucial miRNAs engaged in both diminishing pluripotency state and chondrogenic process (inter alia hsa-miR-525-5p, hsa-miR-520c-3p, hsa-miR-628-3p, hsa-miR-196b-star, hsa-miR-629-star, hsa-miR-517b, has-miR-187). These miRNAs regulate early chondrogenic genes such as: HOXD10, HOXA11, RARB, SEMA3C. These results were confirmed by RT-qPCR analysis. This work contributes to a better understanding of the role of miRNAs directly involved in chondrogenic differentiation of hiPSCs. These data may result in the establishment of a more efficient protocol of obtaining chondrocyte-like cells from hiPSCs.